Studi Bahan Kemas pada Viabilitas Benih Kedelai (Glycine max (L.) Merril.) Selama Periode Simpan Empat Bulan di Wadah Simpan dengan Kapur Tohor - Ermawati, Ermawati (Jurnal Agricultural Biosystem Engineering, 2024)
This study aims to determine the viability of the seeds of packaging materials with high adhesion power, which is higher than those of low adhesion packaging materials in a storage container with quicklime after four months of storage. The research was conducted at the Laboratory of Seed and Plant Breeding, Faculty of Agriculture, University of Lampung from October 2019 to February 2020. This study used a randomized block design (RBD) with four replications. This study used a single unstructured factor, namely the packaging material consisting of aluminum foil (b1), polyethylene (b2), polypropylene (b3), ordinary plastic (b4), brown envelope (b5), and calico cloth (b6). The data analysis used was the Bartlett test to determine the homogeneity of the variety of data between treatments. The addition of data was tested by using the Tukey test, if the assumptions between the data were met, then an analysis of the variety of separation between the mean treatment was carried out by means of a class comparison test at the 5% level and the results showed that the seeds of the packaging material of aluminum foil, polyethylene, polyprophylene, plain plastic, envelope paper, and calico cloth are no different in the container stored with quicklime after four months of storage. High seed viability in aluminum foil, polyethylene, polyprophylene, plain plastic, envelope paper, and calico cloth in the storage room with post-storage air drying agent for four months. The viability of seeds after four months of storage was still high, supported by an average germination value of 92.35%; germination rate 33.16%; normal sprouts dry weight 33.46 mg; water content 6.41% and low electrical conductivity 221.22 µS / cm g. Keywords: packaging materials, seed deterioration, seed viability.